THE USE OF INTERACTIVE LEARNING METHODS IN THE RUSSIAN LANGUAGE AND LITERATURE LESSONS - Kosimova Dilfuza Kurganovna; Abdurakhmanova Sakhibaxon Abdusalamovna (Galaxy International Interdisciplinary Research Journal, 2022)
The paper analyzes the studies on the significance of interactive teaching methods in modern teaching practice. Attention is mainly paid to interactive learning technologies used to enhance student learning and cognitive activity in Russian language and literature classes. An analysis of recent works has shown that interactive teaching methods for younger students correspond more closely to the requirements of the new federal educational standards for primary education. It is argued that the relevance of their use in teaching and educational activities of secondary schools, their importance in shaping students’ universal learning activities and the necessary competencies is proved. The specificity of interaction between teachers and students in the process of implementing interactive teaching methods is revealed, the pedagogical conditions for the success of such interaction are highlighted. The article on the example of the interactive method “Find your morpheme” reveals the features of the organization of cognitive activity of students in the process of interactive interaction between the teacher and students, as well as students among themselves.